2020
DOI: 10.1080/14686996.2020.1808432
|View full text |Cite
|
Sign up to set email alerts
|

A simple in vitro biomimetic perfusion system for mechanotransduction study

Abstract: In mechanotransduction studies, flow-induced shear stress (FSS) is often applied to twodimensional (2D) cultured cells with a parallel-plate flow chamber (PPFC) due to its simple FSS estimation. However, cells behave differently under FSS inside a 3D scaffold (e.g. 10 mPa FSS was shown to induce osteogenesis of human mesenchymal stem cells (hMSC) in 3D but over 900 mPa was needed for 2D culture). Here, a simple in vitro biomimetic perfusion system using borosilicate glass capillary tubes has been developed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Sanat's research showed that MSCs exhibited a high cell proliferation rate when stimulated by intermittent flow at 1.09 mPa, while 10 mPa upregulated osteogenic gene expression (Dash et al, 2020). Xue and Cartmell, (2020) suggested the osteogenic effect of shear stress on MSCs in three-dimensional culture was different from that in the plate. Lower fluid shear stress (1-10 mPa) stimulated MSCs in the scaffold used to simulate a three-dimensional environment to promote the osteogenic differentiation, whereas 100-4,000 mPa was required when the MSCs were cultured in a plate (Xue and Cartmell, 2020).…”
Section: Magnitude and Frequency Of Mechanical Stimulationmentioning
confidence: 99%
“…Sanat's research showed that MSCs exhibited a high cell proliferation rate when stimulated by intermittent flow at 1.09 mPa, while 10 mPa upregulated osteogenic gene expression (Dash et al, 2020). Xue and Cartmell, (2020) suggested the osteogenic effect of shear stress on MSCs in three-dimensional culture was different from that in the plate. Lower fluid shear stress (1-10 mPa) stimulated MSCs in the scaffold used to simulate a three-dimensional environment to promote the osteogenic differentiation, whereas 100-4,000 mPa was required when the MSCs were cultured in a plate (Xue and Cartmell, 2020).…”
Section: Magnitude and Frequency Of Mechanical Stimulationmentioning
confidence: 99%